SilE is an intrinsically disordered periplasmic "molecular sponge" involved in bacterial silver resistance. Issue 5 (7th May 2016) - Asiani, Karishma R.; Williams, Huw; Bird, Louise; Jenner, Matthew; Searle, Mark S.; Hobman, Jon L.; Scott, David J.; Soultanas, Panos
Summary: Ag + resistance was initially found on the Salmonella enetrica serovar Typhimurium multi‐resistance plasmid pMG101 from burns patients in 1975. The putative model of Ag + resistance, encoded by the sil operon from pMG101, involves export of Ag + via an ATPase (SilP), an effluxer complex (SilCFBA) and a periplasmic chaperon of Ag + (SilE). SilE is predicted to be intrinsically disordered. We tested this hypothesis using structural and biophysical studies and show that SilE is an intrinsically disordered protein in its free apo ‐form but folds to a compact structure upon optimal binding to six Ag + ions in its holo ‐form. Sequence analyses and site‐directed mutagenesis established the importance of histidine and methionine containing motifs for Ag + ‐binding, and identified a nucleation core that initiates Ag + ‐mediated folding of SilE. We conclude that SilE is a molecular sponge for absorbing metal ions. Abstract : We show that the periplasmic SilE protein, which is part of the silver resistance machinery of Escherichia coli, is an intrinsically disordered protein in its apo‐form and folds to a holo‐form upon binding to Ag+ ions. Maximal folding is induced upon binding to six Ag+ ions but each holo‐SilE molecule can bind up to eight Ag+ ions. Coordination of Ag+ ions is mediated via conserved histidine and methionine residues arranged in two characteristic motifs (MxxHxxxxxxHxxMxx and HxxMxxxHxxMxx). SilE may act as a metal‐ion chaperone to transport Ag+ ions to the SilABC transporter and/or signal via the histidine kinase sensor SilS to activate the remainder of the silver resistance machinery.